UPAYA MENINGKATKAN KOGNITIF ANAK KELOMPOK A MELALUI MEDIA KARTU WARNADI PAUD MUSLIMAT NU 76 - Syawal, Anisah; Yana, Medi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Based on the results of preliminary observations in PAUD Muslimat NU 76 villages. Baddurih Kec. Pademawu Regency. Pamekasan Researchers found a problem, namely when the introduction of shapes and colors from 10 children in the class, 7 children had difficulty distinguishing the shapes and colors conveyed by the teacher. This can be seen when the teacher asks. This is due to the lack of children recognizing shapes and colors, children find it difficult when asked about shapes and colors and it is difficult to distinguish so that the child's cognitive has not improved. This study aims to improve children's cognitive through the media of color cards.The method used is the Classroom Action Research method with two cycles. The subjects of the study consisted of 10 children 4 girls 6 boys. Research data obtained from Questionnaire, Observation and Documentation. The results of the study were increasing children's cognitive through the media of color cards with the results of Cycle I 2 children getting a score of 2 (20%), 4 children getting a score of 3 (40%) and 4 children getting a score of 4 (40%). Cycle II 9 children get a score of 4 (90%), 1 child gets a score of 3 (10%). So from these results Children's Cognitive can increase. The factor that influences cognitive improvement is the concern of parents for children with several media in the surrounding environment, such as getting to know shapes and colors with objects around them